How does management commitment to safety and employee satisfaction impact safety performance in cleaning workers? - Siti Nurbaya; Halid Hasan (University of Merdeka Malang, 2023)
Management commitment to safety, which reflects managers' dedication to the physical well-being of workers, is a critical component of the safety climate. It serves as the primary indicator of worker safety behavior and plays a crucial role in reducing injuries across diverse job roles. This study aims to investigate the relationship between safety-committed management and employee satisfaction and how this relationship influences safety performance among cleaning staff at PT WIS Malang. We employed purposive sampling to select 113 respondents who completed online questionnaires. Data collected were analyzed descriptively and using inferential statistical analysis. The results of this study underscore the importance of enhancing the role of management in promoting workplace safety and improving employee job satisfaction. We found that management commitment to safety and employee satisfaction have a positive impact on safety performance These findings hold significant practical implications for companies like PT WIS Malang, aiding in the cultivation of a strong safety culture within the organization.